Conservative Accounting and State Ownership: Estimation Model of Conservatism in Indonesian State-Owned Enterprises - Lita Dharmayuni; Denok Sunarsi; Asmar Asmar; Aris Baharuddin (Universitas Negeri Makassar, 2020)
BUMN is considered vital to the national economy, contributing directly to GDP, employment, and market expansion. The contribution of BUMN to State Budget and Expenditure (APBN) revenues in 2018 reached IDR 422 trillion. BUMN companies also control 25% of the capital market capitalization value in Indonesia. BUMN is not much different from other private and public companies; therefore, BUMN is also inseparable from agency conflict. Previous research has shown an inverse effect of government ownership on accounting conservatism and a significant positive relationship between foreign and institutional ownership. The results show that the income level is ‘not persistent’ because the increase has a ‘momentum’ of 43%, which increases in the following year. The results also show that the timely recognition of economic gain (gain) as a component of income is repeating transitory component of income and that the recognition of profits is much more timely than recognition of losses indicates that most of the components of temporary gain from income are not classified by the companies studied. as exceptional or extraordinary.